The Ketogenic Diet: The Ke(y) - to Success? A Review of Weight Loss, Lipids, and Cardiovascular Risk - Boal, Angela H; Kanonidou, Christina (Journal of Cardiology and Cardiovascular Medicine, 2024)
Background: Obesity remains a global epidemic with over 2.8 million people dying due to complications of being overweight or obese every year. The low-carbohydrate and high-fat ketogenic diet has a rising popularity for its rapid weight loss potential. However, most studies have a maximal 2-year follow-up, and therefore long-term adverse events remain unclear including the risk of Atherosclerotic Cardiovascular Disease (ASCVD). Results: Based on current evidence on PubMed and Google Scholar, there is no strong indication ketogenic diet is advantageous for weight loss, lipid profile, and mortality. When comparing a hypocaloric ketogenic diet with a low-fat diet, there may be faster weight loss until 6 months, however, this then appears equivalent. Ketogenic diets have shown inconsistent Low-Density Lipoprotein (LDL) changes; perhaps from different saturated fat intake, dietary adherence, and genetics. Case reports have shown a 2-4-fold elevation in LDL in Familial hypercholesterolaemic patients which has mostly reversed upon dietary discontinuation. There is also concern about possible increased ASCVD and mortality: low (< 40%) carbohydrate intake has been associated with increased mortality, high LDL from saturated fats, high animal product consumption can increase trimethylamine N-oxide, and cardioprotective foods are likely minimally ingested. Conclusion: Ketogenic diets have been associated with short-term positive effects including larger weight reductions. However, by 2 years there appears no significant differences for most cardiometabolic risk markers. Therefore, this raises the question, excluding those who have a critical need to lose weight fast, is this diet worth the potentially higher risks of ASCVD and mortality while further long-term studies are awaited?